2011
DOI: 10.2337/db10-1186
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation Failure Extends to Glycoproteins in Gestational Diabetes Mellitus

Abstract: OBJECTIVEGestational diabetes mellitus (GDM) is a common metabolic disorder of pregnancy. Patients with GDM are at risk for high fetal mortality and gestational complications associated with reduced immune tolerance and abnormal carbohydrate metabolism. Glycodelin-A (GdA) is an abundant decidual glycoprotein with glycosylation-dependent immunomodulatory activities. We hypothesized that aberrant carbohydrate metabolism in GDM was associated with changes in glycosylation of GdA, leading to defective immunomodula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 51 publications
2
25
0
1
Order By: Relevance
“…No reports to date demonstrate dysregulated glycosylation patterns of milk glycoproteins from women with GDM. Yet our results are in line with the finding of Lee et al (20), who reported reduced sialic acid, mannose residues, and impaired immunomodulatory functions of the endometrial glycoprotein, glycodelin A, isolated from amniotic fluid from women with compared with those without GDM. These data suggest that regulated glycemia is required for normal glycosyl transferase activity involving the terminal sialylation of N-linked glycoproteins.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…No reports to date demonstrate dysregulated glycosylation patterns of milk glycoproteins from women with GDM. Yet our results are in line with the finding of Lee et al (20), who reported reduced sialic acid, mannose residues, and impaired immunomodulatory functions of the endometrial glycoprotein, glycodelin A, isolated from amniotic fluid from women with compared with those without GDM. These data suggest that regulated glycemia is required for normal glycosyl transferase activity involving the terminal sialylation of N-linked glycoproteins.…”
Section: Discussionsupporting
confidence: 94%
“…GDM has immediate and lasting consequences in women and their infants exposed to maternal diabetes in utero (14)(15)(16). Hyperglycemia results in aberrant carbohydrate metabolism that contributes to the pathogenesis of the disease in part through increased flux through the hexosamine biosynthetic pathway (17,18) and altered activities of cellular glycosyltransferases and glycosidases (19,20). Yet, very little is known about the effect of GDM on lactation and milk components.…”
Section: Introductionmentioning
confidence: 97%
“…The results of the present study provide evidence that the N-glycan on GLUT4 not only plays a general role in protein stability, but also has a function in GLUT4 sorting and insulin responsiveness. It should be noted that several studies have demonstrated changes of N-glycan profiles under diabetic conditions (43)(44)(45)(46), and the effects of glycan profile alterations, especially in GLUT4, on the insulin resistance phenotype in type 2 diabetes should therefore be carefully investigated in future studies. Clarification of the key factors involved in N-glycan-related intracellular trafficking will be imperative for understanding the precise roles of the N-glycan functions in GLUT4.…”
Section: Discussionmentioning
confidence: 99%
“…Гіперглікемія у разі діабету викликає порушення вуглеводного обміну й утворення кінцевих продуктів глікозилювання -AGEs (з англ. advanced glycation end products), що приз водить до зміни експресії генів і активно-сті клітинних глікозилтрансфераз і глікозидаз -ензимів синтезу глікокон'югатів [7]. Останні відіграють важливу роль у різних біологічних процесах, зокрема, гомеостазі глюкози, конт-ролі якості білків, запаленні, міжклітинному сигналюванні та клітинній адгезії.…”
Section: вступunclassified